SILVICULTURE EVALUATION OF Melia azedarach L. RELATION TO FRUIT SIZE - Hoppe, Juarez Martins (2003)
The objective of the present study was to analyse the field silvicultural behaviour of Melia azedarach L. seedlings, planted at open root condition, derived fron small, medium and big sized fruits. The results show a difference in the growth of plants according to the size of fruits. It is recommended, for the purpose of reforestation, to seed only big sized fruits.